Effectiveness Of Mar'ke Bilar Drink Formulation On Pro- Anti-Free Radicals In The Blood Of Women Of Childbearing Age Operators In Gas Stations - Ginta Siahaan; Fauzi Romeli; R.R. Sri Arini Winarti Rinawati; Suriani br Ginting; Kenya Putri Kasi Sembiring Pandia; Ifta Maulida Tanjung (Medica Hospitalia : Journal of Clinical Medicine, 2025)
BACKGROUND: Women of childbearing age who wortk at gas stations are vulnerable to pollution exposure due to fuel emissions. The workers are susceptible to heavy metal (Pb) poisoning in the fuel content. This can cause health problems such as reproductive disorders, impaired kidney function and can even cause anemia in women. AIMS: To determine the effectiveness of Mar'ke Bilar formulation on Pb, MDA, and SOD in blood. METHOD: The study was Quasi Experimental with a pre and post test group design that allows researchers to see the comparison of the control group with the experimental group. The sample in the study was Women of childbearing age who worked as operators at gas stations with a total of 60 people and were determined based on purposive sampling with inclusion criteria then divided into 4 treatment groups. Data analysis used the T-dependent test to see the differences in each group then continued with the One Way ANOVA and Post Hoc-Tukey tests. RESULT: The results of the study showed that the three of  Mar’ke Bilar formulations were effective in reducing Pb and MDA levels, as well as increasing SOD levels, which are endogenous antioxidant enzymes that are important in the body's defense against oxidative stress. While formula 1 proved to be the most effective in increasing SOD levels. CONCLUSION: Mar'ke Bilar affects blood Pb, MDA, and SOD levels and formulation 1 is the most effective in increasing SOD levels. It is necessary to consume colored foods such as Marke'Bilar which are very good for avoiding diseases caused by free radicals  by air and water pollution, especially those caused by heavy metals.